2009
DOI: 10.4178/epih/e2009003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A Vaccination Rates and Related Factors in a 2005 Population-based Study in Nonsan, Korea

Abstract: OBJECTIVESThe incidence of clinical hepatitis A has increased in young Korean adults since the mid-1990s. Although hepatitis A vaccinations have been administered in private clinics over the past 10 yr, no data exist on the vaccination rate and relating factors.METHODSIn 2005, a population-based survey of 12-35-month-old children was carried out in Nonsan, Korea. An interview survey was completed for 71.3% of the children. All data came from a vaccination card or confirmation from a provider.RESULTSThe hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In Korea, high anti-HAV prevalence of approximately 96% was reported in 1980, and an outbreak affecting a million people has occurred twice in China, in 1983 and 1988. Therefore, Korea and China introduced the HAV vaccine for high risk populations in 1997 22 and 2007 23 , respectively, after which it was included in the national immunization program starting from 2007 for China and 2015 for Korea. As a result, the level of active immunity to HAV via the vaccine increased dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, high anti-HAV prevalence of approximately 96% was reported in 1980, and an outbreak affecting a million people has occurred twice in China, in 1983 and 1988. Therefore, Korea and China introduced the HAV vaccine for high risk populations in 1997 22 and 2007 23 , respectively, after which it was included in the national immunization program starting from 2007 for China and 2015 for Korea. As a result, the level of active immunity to HAV via the vaccine increased dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there have been several arguments that HAV vaccination must be included in the NIP [19]. The number of people receiving two doses of the hepatitis A vaccine in Korea has been estimated at 41.6% based on the number of hepatitis A vaccines sold between 1998 and 2006 [20] and 24.7% based on a 2005 population-based survey [7]. Unfortunately, our study was not designed to provide hepatitis vaccination rates.…”
Section: Discussionmentioning
confidence: 99%
“…Results of two studies have confirmed that 50.6% of children have received the hepatitis A immunization [6], and 42.3% have received the first dose whereas only 24.7% have received both doses of the vaccination [7], indicating that there are significant barriers in accessing immunization services. Yun et al conducted a study to investigate the seroprevalence and vaccination rates in Korea [6].…”
Section: Introductionmentioning
confidence: 99%
“…We conducted face-to-face interviews with subjects' guardians and check record of subject's vaccination card from February to April, 2005 [6,7]. We obtained informed consent to subject's guardians after full explanation about this study.…”
Section: Methodsmentioning
confidence: 99%